Application of virtual reality in neurosurgery: Patient missing. A systematic review. (January 2022) - Vayssiere, Pia; Constanthin, Paul E.; Herbelin, Bruno; Blanke, Olaf; Schaller, Karl; Bijlenga, Philippe
Highlights: Virtual reality. Neurosurgery. Applications. Patients. Abstract: Virtual reality (VR) technology had its earliest developments in the 1970s in the U.S. Air Force and has since evolved into a budding area of scientific research with many practical medical purposes. VR shows a high potential to benefit to learners and trainees and improve surgery through enhanced preoperative planning and efficiency in the operating room. Neurosurgery is a field of medicine in which VR has been accepted early on as a useful and promising tool for neuro-navigation planning. Through recent technological developments, VR further increased its level of immersion, accessibility and intuitive use for surgeons and students and now reveals a therapeutic potential for patients. In this paper, we systematically reviewed the neurosurgery literature regarding the use of VR as an assistance for surgery or a tool centered on patients' care. A literature search conducted according to PRISMA guidelines resulted in the screening of 125 abstracts and final inclusion of 100 original publications reviewed. The review shows that neurosurgeons are now relatively familiar with VR technologies (N = 95 articles) for their training and practice. VR technologies are useful for education, pain management and rehabilitation in neurosurgical patients. Nevertheless, the current patient-oriented use of VR remains limited (N = 5 articles). Successful surgery does not only depend on the surgeon's skills and preparation, but also on patients' education, comfort, empowerment and care. Therefore further clinical research is needed to promote the direct use of VR technologies by patients in neurosurgery.